Single-cell transcriptomes of zebrafish germline reveal progenitor types and feminization by Foxl2l - Chen-wei Hsu; Hao Ho; Ching-Hsin Yang; Yan-wei Wang; Ker-Chau Li; Bon-chu Chung (eLife)
Zebrafish is an important organism for genetic studies, but its early germ cell types and the mechanism of sex differentiation have not been fully characterized. Here, we profiled single-cell transcriptomes and charted a developmental trajectory going from germline stem cells, through early, committed, and late progenitors, to premeiotic and meiotic cells. We showed that the transcription factor Foxl2l was expressed in the progenitor, directing progenitor differentiation toward oocytes. CRISPR-Cas9-mediated mutation of foxl2l produced 100% male fish with normal fertility. Another single-cell profiling of foxl2l-/- germ cells revealed the arrest of germ cell development at the stage of progenitor commitment. Concomitantly, nanos2 transcript (germline stem cell marker) was elevated together with an increase of nanos2+ germ cells in foxl2l mutants, indicating the acquisition of a novel stem cell state. Thus, we have identified developmental stages of germ cells in juvenile zebrafish and demonstrated that zebrafish Foxl2l drives progenitor germ cells toward feminization and prevents them from expressing nanos2.